Elicitation enhances the production of friedelin and epifriedelanol in hairy root cultures of Cannabis sativa L. - Kobtrakul, Khwanlada; Rani, Dolly; Binalee, Asma; Udomlarp, Pattarapol; Srichai, Tatiya; De-Eknamkul, Wanchai; Vimolmangkang, Sornkanok (Frontiers in Plant Science, 2023)
Cannabis sativa L. (hemp) has a global distribution and social impact, and it is widely used as a medicinal plant, food ingredient, and textile fiber. Its roots have received less attention than other parts, especially the inflorescence, leaves, and shoots. Triterpenoids, including friedelin and epifriedelanol, have been found in hemp roots, and their anti-inflammatory effects have been reported. In this study, the potential enhancement of triterpenoid accumulation in the roots of C. sativa by elicitation was examined. Hairy roots were successfully established, and they contained 2.02-fold higher triterpenoid levels than natural roots. Furthermore, hairy roots treated with 75 μM salicylic acid had 1.95-fold higher friedelin levels (0.963 mg/g DW) and 1.4-fold higher epifriedelanol levels (0.685 mg/g DW) than untreated hairy roots. These results suggested that the elucidation of hairy root cultures using an optimized elicitor could represent an alternative strategy to produce the valuable triterpenoids friedelin and epifriedelanol.